2021
DOI: 10.3390/ijerph18105452
|View full text |Cite
|
Sign up to set email alerts
|

Age and Sex-Related Differences in the Tongue Pressure Generated during Maximum Isometric and Swallowing Tasks by Healthy Chinese Adults

Abstract: The aims of this prospective observational study were to investigate age, sex, and factors related to the tongue pressure generated. A correlational research design was used. A total of 150 Chinese people who had a normal swallowing condition were enrolled by convenience sampling. Pressure was measured for each participant during maximum isometric press tasks, as well as for saliva and water swallows (5 mL) at the anterior and posterior tongue. The results illustrated that age has an impact on anterior tongue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Similar to other parts of the body [19,20,25,26], oral function may be significantly affected by aging. Age-related loss of tongue muscle mass as well as reduction in muscle tone accompanied by the accumulation of nonmuscular tissue were suggested to be causes of age-related decreases in TP [27].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to other parts of the body [19,20,25,26], oral function may be significantly affected by aging. Age-related loss of tongue muscle mass as well as reduction in muscle tone accompanied by the accumulation of nonmuscular tissue were suggested to be causes of age-related decreases in TP [27].…”
Section: Discussionmentioning
confidence: 99%
“…18 To this end, PDMS surfaces with a biologically relevant modulus of 150 kPa were employed as surfaces to test the lubrication and adsorption performance of lupine (Lup), pea (Pea), and potato (Pot) proteins, 18 using contact pressures <50 kPa, in the physiological regime. 20–22 Different food-relevant pH and ionic strength conditions that can occur orally were chosen i.e. pH 3.0 and 10 mM NaCl, pH 7.0 and 10 mM NaCl, and pH 7.0 and 50 mM NaCl, a minimal sample set to test the effect of both pH and ionic strength as electrostatic interactions are expected to play a pivotal role in the formation and stability of charged protein films in the oral cavity.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, FFM on soft surfaces enables tribological measurements into a realistic physiological regime, equating to surface contact pressures of <50 kPa at the lower end of the force range covered in this study (specifically at <10 nN normal force), a range experienced in the oral cavity, where tongue pressures of 40–80 kPa are typical in healthy adults. 20–22 Furthermore, this tribological study with plant proteins gives an unprecedented understanding of the dynamics when a plant protein moiety encounters a single papilla in a tongue rather than the entire tongue. Understanding the frictional behaviour of plant proteins and their interaction with mucin-coated surfaces, a representative of many biological surfaces, and in particular oral mucosa, will enable optimizing plant proteins effectively to be used for biomaterial design intended for the oral administration route.…”
Section: Introductionmentioning
confidence: 99%
“…Although the tongue has been considered indefatigable for swallow tasks (given that maximum force capacity of the tongue exceeds the minimum amount of force required for these tasks [43]), it is known that performance of oral motor tasks can be impacted by fatigue [44]. Studies have shown that performance of oral motor tasks can be impacted when muscles are brought to fatigue prior to initiating a functional oral motor task, indicating that fatigued tongue muscles demonstrate impaired performance on motor speech [45] and swallowing tasks [46] when muscle reserves are depleted.…”
Section: Muscle Fatigue and Presbyphagiamentioning
confidence: 99%